HUBUNGAN MOTIVASI BELAJAR DAN KEMANDIRIAN BELAJAR DENGAN HASIL BELAJAR DALAM PEMBELAJARAN BERDIFFERENSIASI PADA MATERI PECAHAN KELAS IV SDN 27 SINGKAWANG - Riska Yulianti; Rosmaiyadi; Dina Anika Marhayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was motivated by the low level of achievement of students' mathematics learning mastery, which based on student learning outcomes did not reach the KKM score. This research aims to describe the relationship between learning motivation and learning independence with mathematics learning outcomes; 2) knowing the achievement of learning outcomes in differentiated learning can help students achieve the minimum completeness criteria (KKM). This research method is correlation research with a quantitative approach. The research population was all fourth grade students at SDN 27 Singkawang. The sample in this research was class IV A students at SDN 27 Singkawang, totaling 29 students. Data was obtained through learning outcomes test instruments as well as questionnaires on student learning motivation and learning independence. The data analysis techniques used are Pearson product moment correlation, multiple correlation, and one sample t-test. The results of the research show that 1) There is a relationship between learning motivation and student learning outcomes, obtained by the Pearson product moment correlation coefficient of 0.783 which is in the strong relationship category. 2) There is a relationship between learning independence and student mathematics learning outcomes obtained by the Pearson product moment correlation coefficient. amounting to 0.902 which is in the strong relationship category. 3) There is a relationship between learning motivation and learning independence and student learning outcomes, resulting in a multiple correlation coefficient of 0.906 which is in the relationship category. 4) From the results of calculating student learning outcomes data, the coefficient results are one sample t-test with Asymp. Sig (2-tailed) = 0.000, then 0.000 < 0.05 so it can be concluded that the ability to understand concepts in differentiated learning can help class IV A students at SDN 27 Singkawang achieve the minimum completeness criteria (KKM).